2017
DOI: 10.1007/s00330-017-5118-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based quantitative texture analysis of CT images of small renal masses: Differentiation of angiomyolipoma without visible fat from renal cell carcinoma

Abstract: • Although conventional CT is useful for diagnosis of SRMs, it has limitations. • Machine-learning based CT texture analysis facilitate differentiation of small AMLwvf from RCC. • The highest accuracy of SVM-RFE+SMOTE classifier reached 93.9 %. • Texture analysis combined with machine-learning methods might spare unnecessary surgery for AMLwvf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 40 publications
7
128
1
1
Order By: Relevance
“…Kurtosis and entropy could, respectively, represent the shape and irregularity of the voxel distribution, which could represent tumor heterogeneity from different perspectives . Liu SL and Feng Z reported that kurtosis and entropy based on CTTA could help differentiate benign and malignant tumors. However, we did not find significant difference in kurtosis and entropy between PDAC and atypical pNET.…”
Section: Discussionmentioning
confidence: 99%
“…Kurtosis and entropy could, respectively, represent the shape and irregularity of the voxel distribution, which could represent tumor heterogeneity from different perspectives . Liu SL and Feng Z reported that kurtosis and entropy based on CTTA could help differentiate benign and malignant tumors. However, we did not find significant difference in kurtosis and entropy between PDAC and atypical pNET.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the first 19 features achieved the highest AUC (0.9819) with an accuracy of 92.59%, whereas the first nine features achieved the highest accuracy (92.59%) with an AUC of 0.9556 in classification. Owing to the imbalance of sample size between two groups, the AUC could better evaluate the comprehensive performance of the classifier for the differentiation task . Therefore, the subset consisting of 19 top‐ranked features was determined as the optimal subset …”
Section: Resultsmentioning
confidence: 99%
“…After 10 subsets are successively validated, one round classification is finished and the performance can be obtained. Owing to the random allocation of the 10‐fold subsets, only one round classification may not well reflect the overall performance of the samples . Instead, the procedures above are usually repeated for 100 rounds, and the final average performance can be achieved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the visual characteristics of CT imaging are insufficiently specific or overlap among various SRMs; for instance, between fat‐poor angiomyolipoma and renal cell carcinoma subtypes. Recently, quantitative methods have been developed to detect subtle variations beyond visual assessment on CT images…”
mentioning
confidence: 99%